EFL Students' Perception of Wordwall.net Used as Media for Learning English Grammar - Laily Wahyuni Ilahi; Cahya Komara, S.Pd., M.Hum.; Yusuf Ismail, S.Pd. (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Recently, technology utilization is remarkably vital in 21st century learning. Many EFL teachers integrate technology in their teaching and learning process for gaining not only their students’ competence but also their students’ engagement. This technology is commonly known by learning media, and it is used either in the offline or online learning situation. Wordwall.net is one of it; a learning media that can be applied in EFL learning context. This study aimed to investigate EFL students’ perception of Wordwall.net used particularly in learning English grammar. The research was conducted in a form of quantitative approach by using survey design with sample of 129 respondents from one private Senior High School in Jakarta. The data was collected through a close-ended questionnaire with the Likert scale and analyzed by using SPSS Version 25. The findings showed that the use of Wordwall.net was convincingly positive for the EFL students on the aspects of feeling (89.6%), attitude (67.3%), and engagement (77.4%). Keywords: EFL Students, Grammar, Perception